Public inclination towards waste segregation programme (A case study on the effectiveness of #Asingkan campaign in Klang Valley) / Intan Abida Abu Bakar, Srikumar K. Ramayan, Vijaya Sooria Sangaran. - Abu Bakar, Intan Abida; Ramayan, Srikumar K.; Sangaran, Vijaya Sooria (Universiti Teknologi MARA, Perak, 2020)
This paper investigates the effectiveness of the #Asingkan Waste Segregation Campaign in Klang Valley area. In September 2015, the Urban Well-being, Housing and Local Government Ministry began enforcing Act 672 of the Solid Waste and Public Cleansing Management Act 2007. The Act makes it compulsory for residents to separate their solid wastes according to categories of paper, plastics and others or face fines between RM50 and RM500. This Segregation programme affects those living in Putrajaya and Kuala Lumpur, Johor, Malacca, Negeri Sembilan, Kedah, Perlis and Pahang. The main objective of this research is to investigate the awareness level of public towards waste segregation programme and analyse the effectiveness of #Asingkan campaign. Data from questionnaires and focus group discussions indicate that the waste segregation programme and the #Asingkan campaign are not running effectively. The Malaysian Government should find the right approach to educate and change the public's attitude in order to make sure this programme successful.